ANGEL FISH ( PTEROPHYLLUM SCALARE ) - STUNTED GROWTH AND SWIMMING ABNORMALITIES - A REPORT - S. David Kingston; J. Mary Sophia; V. Viji (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Abnormalities in size and growth has been observed in the young ones of angel fish (Pterophyllum scalare) of the same brood. Morphological measurements confirm the abnormalities in the affected specimens. As per the reports available, methylene blue treatment during the early life stages may have a teratogenic effect which led to such conditions in angel fish.